2021
DOI: 10.1111/cas.14984
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase confers temozolomide resistance by regulation of exosome secretion and circular RNA composition in glioma

Abstract: Temozolomide (TMZ) resistance is the main challenge in the management of glioma patients. Heparanase can mediate the secretion and function of exosomes, which are considered to be a promising molecular delivery system for cancer therapy. Therefore, this study aimed to investigate whether heparanase‐mediated delivery of exosomes was related to TMZ resistance of glioma. Heparanase was upregulated in TMZ‐resistant glioma cells, and overexpression of heparanase led to increased resistance of U87 cells to TMZ. Knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Over the last decade, circRNAs have been reported as important mediators related to the development of chemoresistance in various tumors, such as gastric cancer [ 172 , 173 ], non-small-cell lung cancer [ 174 ], esophageal cancer [ 175 ], pancreatic cancer [ 176 , 177 ], colorectal cancer [ 152 154 , 178 ], glioma [ 179 , 180 ], and osteosarcoma [ 181 , 182 ]. However, there are few studies on exosomal circRNA drug resistance to tumors, and the mechanism remains unknown.…”
Section: Main Textmentioning
confidence: 99%
“…Over the last decade, circRNAs have been reported as important mediators related to the development of chemoresistance in various tumors, such as gastric cancer [ 172 , 173 ], non-small-cell lung cancer [ 174 ], esophageal cancer [ 175 ], pancreatic cancer [ 176 , 177 ], colorectal cancer [ 152 154 , 178 ], glioma [ 179 , 180 ], and osteosarcoma [ 181 , 182 ]. However, there are few studies on exosomal circRNA drug resistance to tumors, and the mechanism remains unknown.…”
Section: Main Textmentioning
confidence: 99%
“…Here, we summarized the contribution of circRNAs to chemoresistance in glioma patients ( Table 5 ). It has been shown that exosomal hsa_circ_0042003, mediated by heparanase transfers from temozolomide (TMZ)-resistant glioma cells to drug-sensitive cells, which contributes to TMZ resistance in glioma ( 113 ). In glioma, exosomal circ_0072083 modulates NANOG and ALKBH5 by targeting miR-1252-5p and demethylation to control TMZ resistance ( 114 ).…”
Section: Circrnas and Drug Resistancementioning
confidence: 99%
“…It has been demonstrated to reduce the sensitivity of gliomas to TMZ ( 146 ). Exosomes derived from TMZ-resistant glioma cells mediate the transfer of chemoresistance to TMZ-sensitive glioma cells via circ_0042003 ( 147 ). Therefore, exosomal circRNAs have an undeniable role in TMZ resistance.…”
Section: Circrnas and Drug Resistance Of Gliomasmentioning
confidence: 99%